Impact Resistance of Polypropylene Fibre-Reinforced Alkali–Activated Copper Slag Concrete - Saavedra-Flores, E; Avudaiappan-, S (Multidisciplinary Digital Publishing Institute (MDPI), 2021)
Copper slag (CS) is produced during the smelting process to separate copper from copper ore. The object of the experimental research is to find the optimum percentage of CS and PPF volume fraction when CS replaces fine aggregate, and PPF volume fraction when subjected to impact loading. Copper slag was incorporated as 20%, 40%, 60%, 80% and 100% with PPF of 0.2–0.8% with 0.2% increment. The number of blows on failure of the specimen increases as the fibre volume increases. In addition, the energy absorption of composite concrete is higher than that of ordinary concrete. Concrete with up to 40% CS and 0.6% PPF volume shows a 111.72% increase in the number of blows for failure as compared to the control specimen. The impact resistance at failure was predicted by regression analysis, and very high regression coefficients of 0.93, 0.98 and 0.98 were obtained respectively at 7-, 14-and 28-days curing. In addition to regression analysis, a two-parameter Weibull distribution analysis was used to obtain reliable data on the number of blows at first cracking and eventual failure. The energy absorption at 28-day curing period is 1485.81 Nm which is 284% higher than the control mix. Based on the findings, it can be inferred that adding CS up to 60% densifies the microstructure due to its pozzolanic activity, while polypropylene fibre acts as a micro reinforcement, increasing the number of blows. © 2021 by the authors. Licensee MDPI, Basel, Switzerland.